2019
DOI: 10.1093/heapro/daz128
|View full text |Cite
|
Sign up to set email alerts
|

Professional football clubs’ involvement in health promotion in Spain: an audit of current practices

Abstract: Professional football clubs' involvement in health promotion in Spain: An audit of current practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Our findings correspond with and expand previous studies investigating existing healthpromotion programmes [24], overall CSR engagement and integration in football clubs [25,28,29,37] and decision-making processes in foundations associated with professional football clubs in the UK [20,26]. In light of the integrative framework of CSR in football clubs [25], both RCT and pilot club representatives appeared to understand their club's adoption process of EuroFIT in a wide context considering both program (e.g., evidence base of program), operational (e.g., club infrastructure and human resources), social (e.g., societal needs) and strategic (e.g., club values and business and social objectives) motives irrespective of existing healthpromotion programs and organizational structure.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings correspond with and expand previous studies investigating existing healthpromotion programmes [24], overall CSR engagement and integration in football clubs [25,28,29,37] and decision-making processes in foundations associated with professional football clubs in the UK [20,26]. In light of the integrative framework of CSR in football clubs [25], both RCT and pilot club representatives appeared to understand their club's adoption process of EuroFIT in a wide context considering both program (e.g., evidence base of program), operational (e.g., club infrastructure and human resources), social (e.g., societal needs) and strategic (e.g., club values and business and social objectives) motives irrespective of existing healthpromotion programs and organizational structure.…”
Section: Discussionsupporting
confidence: 92%
“…Adoption of health-promotion interventions within professional football organisations is a process where designated managers or decision-makers in clubs or their foundations (a charitable arm of football clubs) decide whether they should commit to delivering a specific project [20,21]. Despite recent encouragement from the Union of European Football Associations (UEFA), to adopt evidence-based community intervention projects [22] and the focus on health as part of clubs' CSR provision [1,23], relatively few professional football organisations are adopting such health-promotion programmes in real-world settings [24]. A recent audit of Spanish football clubs reported that club representatives had contrasting views about their respective club's role in health promotion provision; most viewed health-promoting CSR activities as outside their core business as a football club, while others believed it supported the club's social role [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sports can be tightly interwoven with formative life experiences (Schofield & Tolson, 2010), and being part of a team can reinforce identity, personal value and offer acceptance (Weiss, 2001). Harnessing men's interest in sport can facilitate uptake of physical and mental health interventions (Bruun et al, 2014;Carone et al, 2016;Curran et al, 2017), and football clubs become vessels to share public health messages with men (Lozano-Sufrategui et al, 2019;Pringle et al, 2014).…”
Section: Introductionmentioning
confidence: 99%